Storyworlds: hide and seek - Reid, Dee (Heinemann UK, 2009)
*Hide and Seek* is a playful story where children enjoy the classic game of hide-and-seek, learning lessons about patience, creativity, and teamwork as they take turns hiding and searching for each other. The story emphasizes the joy of play and the excitement of discovering hidden surprises.